Combining ability of CMS-lines of grain sorghum based on A1, A2, A3, A4, 9E and M-35-1A types of сytoplasmic male sterility - O. P. Kibalnik (Вавиловский журнал генетики и селекции)
Cytoplasmic male sterility (CMS) is widely used in heterosis breeding of crops, including sorghum. In breeding work, “Rossorgo” uses early maturing source material adapted to the conditions of cultivation in the Lower Volga region, a collection CMS-lines with different types of sterile cytoplasm (A1, A2, A3, A4, 9E, M-35-1A) and varieties of grain sorghum. To create heterosis hybrids, it is required to identify the parental form with a high combining ability. Hybrids were derived from CMS-lines: A1 O-Yang 1, A2 KVV 114, A2 Vostorg, A2 Tamara, A3 Feterita 14, A4 KP 70, M-35-1A and 9E Pischevoe 614. The pollinators (testers) to crossing included varieties of grain sorghum: Mercury, Ogonek, Avans, Topaz, Volzhskoe 615, Pischevoe 35, Volzhskoe 4. The tests were conducted on the experimental field of “Rossorgo” in 2015–2016. Meteorological conditions during the studies differed in the amount of precipitation and the sum of active temperatures. Combining ability (CA) of the starting material was determined by the method of topcross. It was found that the manifestation of traits (plant height, parameters of the panicle, the weight of grains in one panicle and 1000 grains, yield) in sorghum is controlled by genes with additive effect. For further breeding for heterosis, CMS-lines (A1 O-Yang 1, A3 Feterita 14 and A4 KP 70) were selected with strong high effects of GCA on the main breeding grounds stable for years. High CA also characterized varieties Volzhskoe 4 (height of plant, weight of grains in one panicle and yield), Avans and Topaz (mass of 1000 grains and yield). For competitive variety trials, promising F1 hybrids of sorghum with high SCA effects for yield and weight of 1000 grains were identified. Hybrids to create synthetic varieties-populations were proposed.